Salinity Tolerance in Adults of Three Unionoid Mussel Species (Margaritifera sp., Lanceolaria oxyrhyncha and Nodularia douglasiae) and Glochidia of Two Species (Nodularia douglasiae and Buldowskia sp.) in Experimental Tanks and the Occurrence of Two Types of Glochidia in Fish in a Brackish Lake - Itoh, Toshishige; Kakino, Wataru; Ichikawa, Keisuke; Narita, Masaru; Takeuchi, Motoi (Venus (Journal of the Malacological Society of Japan), 2023)
Salinity tolerances of unionoid mussels were examined in experimental tanks, and their habitats were investigated in a brackish lake. In an experimental study involving adults of three mussel species, Margaritifera sp., Lanceolaria oxyrhyncha and Nodularia douglasiae, water salinity was gradually increased from 3 to 12 psu. At 3 psu, all the specimens of Margaritifera sp. died. All the specimens of L. oxyrhyncha died in the range 6–9 psu, but N. douglasiae survived. At 9–12 psu, all the subject specimens died. In subsequent experiments on Margaritifera sp. and N. douglasiae, individuals were kept at lethal salinity (3 and 9 psu respectively) for 3 h to 2 d and then moved to safe salinity (0 psu), and almost all survived. In experiments that manipulated salinity at 1–2 d intervals from a safe level (0 psu) to a lethal level (9 psu) to safe level, and many specimens of N. douglasiae survived. However, in experiments that manipulated salinity at 1–2 d intervals from a safe level (3 psu) to a lethal level (9 psu) to safe level, many specimens of N. douglasiae died. For the experimental study on juveniles, we manipulated the salinity levels from 0 to 22–33 psu then lowered them to 0 psu within a few days. We confirmed that several glochidia of N. douglasiae and Buldowskia spp. successfully detached from their hosts and metamorphosed. During these experiments, five euryhaline fish species, Plectorhinchus cinctus and Scatophagus argus for N. douglasiae and Terapon jarbua, Paralichthys olivaceus and Paraplagusia japonica for Buldowskia sp., were newly confirmed as host species. Field research on the host species of Glochidia was conducted in the brackish Lake Ogawara in Aomori Prefecture. The number of glochidia that parasitized the fish was determined at the infected sites on the fish, as well as the glochidial encystment rate, using formalin-fixed specimens collected from the lake. Two types of glochidia were found to be parasitic in several fish species examined, both from the known host species Hypomesus nipponensis, Pseudaspius hakonensis, and Gymnogobius castaneus, and from species not previously known to be hosts, namely Platichthys stellatus, and Mugil cephalus. Taken together, these results show that adult mussels could not survive at water salinity levels above 3–6 psu but that glochidia on a host were able to survive at high salinities. This suggests that these mussel species might expand their populations to other geographical areas through brackish and sea environments via host fish migration during the glochidium stage.